2021
DOI: 10.3389/fimmu.2021.732006
|View full text |Cite
|
Sign up to set email alerts
|

International Prognostic Index-Based Immune Prognostic Model for Diffuse Large B-Cell Lymphoma

Abstract: BackgroundThe International Prognostic Index (IPI) is widely used to discriminate the prognosis of patients with diffuse large B-cell lymphoma (DLBCL). However, there is a significant need to identify novel valuable biomarkers in the context of targeted therapy, such as immune checkpoint blockade (ICB).MethodsGene expression data and clinical DLBCL information were obtained from The Cancer Genome Atlas and Gene Expression Omnibus datasets. A total of 371 immune-related genes in DLBCL patients associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…); abundance is positively correlated ( 31 ). SYNDIG1 is a prognostic immune factor in diffuse large B-cell lymphoma and breast cancer ( 32 , 33 ). DACT1 belongs to the DACT (Disheveled-associated antagonist of β-catenin) family and is a methylation biomarker for DACT1 in esophageal squamous cell carcinoma ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…); abundance is positively correlated ( 31 ). SYNDIG1 is a prognostic immune factor in diffuse large B-cell lymphoma and breast cancer ( 32 , 33 ). DACT1 belongs to the DACT (Disheveled-associated antagonist of β-catenin) family and is a methylation biomarker for DACT1 in esophageal squamous cell carcinoma ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL‐12 plays a central role in the cellular and humoral pathways, which is mainly produced by antigen‐presenting cells and acts on T cells and natural killer (NK) by inducing IFN‐γ production 72,73 . Recently, the IPI‐based immune prognostic model based on eight genes including IL12A had independent prognostic significance in DLBCL patients, which provided an immunological perspective for elucidating the tumor progression mechanism of DLBCL, and were also useful for DLBCL immunotherapy 74 . We found that the GC genotype had the lowest OS, and the GG and CC genotypes had similar OS levels in lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
“… 8 We do not know potential unknown genetic causes because we have not performed whole‐genome sequences for germline and somatic genetic variants, which is beyond the scope of this case report. 9 …”
Section: Discussionmentioning
confidence: 99%